Information of Nursing School Students in Tartous Governorate about Breast Self-Examination - عجي, سناء عبد الحميد; اصبيره, ولاء; زمزم, سوزان (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: Breast cancer is one of the most common cancers among women worldwide. About one million cases are diagnosed worldwide each year. Early detection is one of the most important factors that increase the rate of recovery and survival. Breast self-examination is an important, easy, inexpensive and time-consuming procedure, and a woman can do it herself at home after the age of twenty for early detection of breast cancer. Aim: This descriptive study aimed to determine the extent to which female students in the School of Nursing and Midwifery in Tartous apply the breast self-examination. Using a systematic random sample which amounted to (122) nursing students from the three years from 26/6/2022 to 7/7/2022. The results showed that about three quarters of the sample (75.4%) had knowledge of breast self-examination and the main source of this knowledge was the Internet (83.7%). (61.1%) of the cases did not know the method of the procedure, and half of the women who used to conduct a breast self-examination performed it irregularly on a monthly basis, and less than half of the participants who knew the procedure did the examination a week after the menstruation, and none of the participants knew the correct technique for the examination. The study recommended the necessity of conducting continuous training programs to train female students on the method of breast self-examination, and focusing on the role of the medical and nursing staff as a source of information related to this examination.